Discussion on Environmental Protection and Enterprise Economic Development. Issue 5 (March 2019) - Zhang, Huimin; Jiang, Na
Abstract: 2018 is the 40th anniversary of the reform and opening up. Today, people's lives are getting richer and the country is becoming stronger and stronger. These are the results of the rapid development of social economy, and the development of enterprise economy has made an important contribution to the development of social economy. At the time of rapid economic development, the natural environment has been destroyed and polluted, which is caused by the lack of adequate attention to environmental protection in the process of enterprise development. Environmental protection has become a social problem that needs to be solved urgently nowadays. It is also the responsibility and important motive force that enterprises should have. This paper discusses environmental protection and enterprise economic development from the causes of environmental deterioration, the relationship between environmental protection and enterprise development, and the obstacles to the implementation of enterprise environmental protection management.